2018
DOI: 10.1093/ntr/nty103
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of E-Cigarette Use Among Youth and Young Adults: Review of the Impact of E-Cigarettes on Cigarette Smoking

Abstract: The present article provides a review of the impact of e-cigarette use on subsequent cigarette smoking among youth and YAs. Studies presented here suggest that e-cigarette use among non-smokers is associated with subsequent cigarette smoking, but study designs are subject to numerous limitations. Future research should focus on addressing the characteristics that put youth and YAs at risk of using either product and how appeal and accessibility of these products are related to product use in order to inform fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 51 publications
4
70
0
8
Order By: Relevance
“…For example, research examining the impact of e-cigarette and cigarette prices on cigarette consumption among young low-risk and high-risk non-smokers, as well as among cigarette smoking youth and young adults, is needed. The controversial 53 yet growing body of evidence that links e-cigarette use among youth to later cigarette use54 53 underscores the need to continue to monitor the impact of price on both e-cigarette and cigarette use among youth and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research examining the impact of e-cigarette and cigarette prices on cigarette consumption among young low-risk and high-risk non-smokers, as well as among cigarette smoking youth and young adults, is needed. The controversial 53 yet growing body of evidence that links e-cigarette use among youth to later cigarette use54 53 underscores the need to continue to monitor the impact of price on both e-cigarette and cigarette use among youth and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that e-cigarette use among never smoking children and adolescents is associated with later smoking [32], including within the UK [33]. However, as the authors acknowledge [33], much of this observed association may reflect residual confounding by shared risk factors, rather than one causing the other.…”
Section: Introductionmentioning
confidence: 93%
“…number of friends/family members that smoke) or intrapersonal (e.g. such impulsivity, sensation seeking, rebellion) [17]. One paper [34] only included variables from one domain, while eight papers [33,36,41,44,45,48,49,51] included variables from two domains, and ten papers [31,32,37,38,40,42,43,46,47,50] included variables from all three domains.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
“…Soneji et al using seven studies found that e-cigarette use is associated with an increased risk of future cigarette smoking initiation and current cigarette smoking in young people aged 14-30 years, even after adjusting for potential confounding by demographic, psychosocial, and behavioural risk factors [16]. Glasser et al concluded that e-cigarette use is associated with subsequent smoking in young people [17]. Aladeokin and Haighton included three studies in their meta-analysis and showed that United Kingdom (UK)-based adolescents who use ecigarettes were six times more likely to smoke tobacco cigarettes.…”
Section: Introductionmentioning
confidence: 99%